Belize : 2018 Article IV Consultation-Press Release; Staff Report; Informational Annex; Debit Sustainability Analysis and Statement by the Executive Director for Belize. (IMF Staff Country Reports; Country Report ;, 2018)
Belize's economic growth has slowed over the last five years, following decades of outperforming regional peers. As in other countries in the region, a central challenge is exiting the cycle of low growth and elevated public debt. Belize's 2017 debt rescheduling provided cash flow relief. In March 2017, the government reached a restructuring agreement with private external bondholders on its USD 526 million bond (about 30 percent of GDP).1 As part of the agreement, the authorities committed to tighten the fiscal stance by 3.0 percentage points in FY2017/18 and to maintain a primary surplus of 2.0 percent of GDP for the subsequent three years. The authorities are delivering on these commitments and have made progress in implementing recent Article IV recommendations (Annex I).